2020
DOI: 10.31067/0.2019.161
|View full text |Cite
|
Sign up to set email alerts
|

Bir Geçerlik ve Güvenirlik Çalışması: Öz-Yeterlik için Semptom Yönetim Ölçeği

Abstract: Bu araştırmanın amacı; Öz-Yeterlik için Semptom Yönetim Ölçeği'nin Türkçe geçerlik ve güvenilirlik çalışmasını yaparak bu ölçeği ulusal literatüre kazandırmaktır. Gereç-Yöntem: Araştırmada, 13 ifadeden oluşan Öz-Yeterlik için Semptom Yönetim Ölçeği kullanılmıştır. Öncelikle ölçeğin Türkçe geçerlik ve güvenilirlik çalışmalarının yapılabilmesi için dil ve kapsam geçerlikleri yapılmış, dil ve kapsam geçerlikleri sonucunda oluşan Türkçe ölçek; iki farklı hastanede tedavi gören kronik hastalığa sahip bireylere uygu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is noteworthy that the caregiver practices focus on being aware and preventing the development of symptoms, and managing the process. In recent years, specific scale studies related to the effect of symptom management on both patient and caregiver have shown the importance of symptom management (18,19). Protection, treatment compliance, and symptom management are subjects in the education given to patients and their families by healthcare professionals (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the caregiver practices focus on being aware and preventing the development of symptoms, and managing the process. In recent years, specific scale studies related to the effect of symptom management on both patient and caregiver have shown the importance of symptom management (18,19). Protection, treatment compliance, and symptom management are subjects in the education given to patients and their families by healthcare professionals (20,21).…”
Section: Discussionmentioning
confidence: 99%